Legal Efforts in Handling Consumer Disputes at the Consumer Dispute Settlement Body (BPSK) in Indonesia - M. Sunandar Yuwono; Ade Saptomo (Pelopor Publikasi Akademika, 2024)
Consumer disputes are issues that frequently arise in the relationship between consumers and businesses. In Indonesia, the Consumer Dispute Settlement Body (BPSK) plays a vital role in addressing these disputes. The legal efforts available through BPSK are regulated under Law of the Republic of Indonesia No. 8 of 1999 on Consumer Protection, which provides a legal framework for dispute resolution that is simple, fast, and low-cost. The dispute resolution process at BPSK includes mediation, binding decisions, and procedures regulated by the Ministry of Trade Regulation No. 11 of 2016. This research uses a qualitative approach with data collection techniques through in-depth interviews, observations, and document analysis. This study aims to analyze the effectiveness of the legal efforts undertaken by BPSK in handling consumer disputes, as well as the challenges faced in its implementation. The findings indicate that although BPSK offers better access for consumers, there are still barriers regarding socialization, resource capacity, and community legal awareness. This research is expected to provide recommendations for improving the consumer dispute resolution system in Indonesia.